Taurine and Ginsenoside Rf Induce BDNF Expression in SH-SY5Y Cells: A Potential Role of BDNF in Corticosterone-Triggered Cellular Damage - Won Jin Lee; Gyeong Hee Lee; Jinwoo Hur; Hyuk Gyoon Lee; Eunsu Kim; Jun Pil Won; Youngjae Cho; Mi-Jung Choi; Han Geuk Seo (Molecules, 2020)
This study shows that taurine and ginsenoside Rf act synergistically to increase the expression of brain-derived neurotrophic factor (BDNF) in SH-SY5Y human neuroblastoma cells in a dose- and time-dependent manner. The increase of BDNF mRNA by taurine and ginsenoside Rf was markedly attenuated by inhibitors of extracellular signal-regulated kinase and p38 mitogen-activated protein kinase. In addition, taurine and ginsenoside Rf protected cells from corticosterone-induced BDNF suppression and reduced cell viability and lactate dehydrogenase release. The results from this study showed that combined treatment with both taurine and ginsenoside Rf enhanced BDNF expression and protected cells against corticosterone-induced damage.